Combating ozone stress through N fertilization: A case study of Indian bean (Dolichos lablab L.) - Sahoo, Ansuman; Madheshiya, Parvati; Mishra, Ashish Kumar; Tiwari, Supriya (Frontiers in Plant Science, 2023)
The present study investigates the efficiency of nitrogen (N) amendments in the management of ozone (O3) stress in two varieties (Kashi Sheetal and Kashi Harittima) of Hyacinth bean (Dolichos lablab L.). Two O3 concentrations, ambient (44.9 ppb) and elevated (74.64 ppb) were used, and each O3 concentration has 4 nitrogen (N) dose treatments viz recommended (N1), 1.5 times recommended (N2), 2 times recommended (N3) and no nitrogen, which served as control (C). The experiment established Kashi Sheetal as O3 tolerant, as compared to Kashi Harittima. N amendments were effective in the partial amelioration of O3 stress, with N2 being the most effective nitrogen dose, at both ambient and elevated O3 concentrations. The O3-sensitive variety, Kashi Harittima, responded more positively to N treatments, at both O3 concentrations. The positive effect of N amendments is attributed to the stimulated antioxidative enzyme activity, rather than the biophysical processes like stomatal conductance. Strengthened defense upon N amendments was attributed to the enhanced activities of APX and GR in Kashi Sheetal, while in Kashi Harittima, the two enzymes were coupled by SOD and CAT as well, during the reproductive phase. Yield (weight of seeds plant-1) increments upon N (N2) amendments were higher in Kashi Harittima (O3 sensitive), as compared to Kashi Sheetal (O3 tolerant) at both ambient and elevated O3 concentration, due to higher antioxidant enzymatic response and greater rate of photosynthesis in the former.